Mutational characterization of Omicron SARS-CoV-2 lineages circulating in Chhattisgarh, a central state of India - Singh, Pushpendra; Sharma, Kuldeep; Shaw, Dipika; Bhargava, Anudita; Negi, Sanjay Singh (Frontiers in Medicine, 2023)
Introduction The emergence of the Omicron SARS-CoV-2 variant from various states of India in early 2022 has caused fear of its rapid spread. The lack of such reports from Chhattisgarh (CG), a central state in India, has prompted us to identify the Omicron circulating lineages and their mutational dynamics. Materials and methods Whole-genome sequencing (WGS) of SARS-CoV-2 was performed in 108 SARS-CoV-2 positive combined samples of nasopharyngeal and oropharyngeal swabs obtained from an equal number of patients. Results All 108 SARS-CoV-2 sequences belonged to Omicron of clade 21L (84%), 22B (11%), and 22D (5%). BA.2 and its sub-lineages were predominantly found in 93.5% of patients, BA.5.2 and its sub-lineage BA.5.2.1 in 4.6% of patients, and B.1.1.529 in 2% of patients. Various BA.2 sub-lineages identified were BA.2 (38%), BA.2.38 (32%), BA.2.75 (9.25%), BA.2.56, BA.2.76, and BA.5.2.1 (5% each), BA.2.74 (4.6%), BA.5.2.1 (3.7%), BA.2.43 and B.1.1.529 (1.8% each), and BA.5.2 (0.9%). Maximum mutations were noticed in the spike (46), followed by the nucleocapsid (5), membrane (3), and envelope (2) genes. Mutations detected in the spike gene of different Omicron variants were BA.1.1.529 (32), BA.2 (44), BA.2.38 (37), BA.2.43 (38), BA.2.56 (30), BA.2.74 (31), BA.2.75 (37), BA.2.76 (32), BA.5.2, and BA.5.2.1 (38 similar mutations). The spike gene showed the signature mutations of T19I and V213G in the N-terminal domain (NTD), S373P, S375F, T376A, and D405N in receptor-binding domain (RBD), D614G, H655Y, N679K, and P681H at the furin cleavage site, N764K and D796K in fusion peptide, and Q954H and N969K in heptapeptide repeat sequence (HR)1. Notably, BA.2.43 exhibited a novel mutation of E1202Q in the C terminal. Other sites included ORF1a harboring 13 mutations followed by ORF1b (6), ORF3a (2), and ORF6 and ORF8 (1 mutation each). Conclusion BA.2 followed by BA.2.38 was the predominant Omicron lineage circulating in Chhattisgarh. BA.2.75 could supersede other Omicron due to its mutational consortium advantage. The periodical genomic monitoring of Omicron variants is thus required for real-time assessment of circulating strains and their mutational-induced severity.